KAJIAN LINGUISTIK FUNGSIONAL SISTEMIK: ANALISIS HUBUNGAN SISTEM TRANSITIVITAS DAN KONTEKS SITUASI DALAM PIDATO PRESIDEN JOKOWI SOAL PENANGANAN VIRUS CORONA - Muhamad Faisal Assyuza; Anwar Miftahulkhairah (Jurnal CULTURE (Culture, Language, and Literature Review), 2021)
The study aims to describe the Systemic Functional Linguistics (SFL) study regarding the relationship between the transitivity process system and sirkumstan of the situation in President Jokowi's speech about the handling of the COVID-19. This research is a descriptive study with a qualitative approach. The source that used to be the object of this study was the text of President Jokowi's speech about the handling of the COVID-19. Data collection did not involve the author directly, but data was obtained from the Kabar24 website which was uploaded on March 15, 2020. The data collection technique used in this study was the reading comprehension technique which was carried out with a concentration on the object to be studied. The results showed that the total number of processes was 57 data. The number of material process occurrences was 31 data with an emergence percentage of 54%, then followed by the Mental process with 11 data occurrences, with an appearance percentage of 19%, the Relational process the number of occurrences was 6 data with an appearance percentage of 11%, the Behavioral process the number of occurrences was 3 data with an occurrence percentage of 5%, the Verbal process was 2 data with an appearance percentage of 4%, and finally the Existential process was 4 data with an appearance percentage of 7%. The number of sirskumstan recorded in time 1 and place 10.